2014
DOI: 10.1016/j.jfma.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic differentiation of dental pulp stem cells to neuron-like cells in dopaminergic and motor neuronal inductive media

Abstract: These findings suggest that in response to the neuronal inductive stimuli, a greater proportion of DPSCs stop proliferation and acquire a phenotype resembling mature neurons. Such neural crest-derived adult DPSCs may provide an alternative stem cell source for therapy-based treatments of neuronal disorders and injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 37 publications
4
73
0
3
Order By: Relevance
“…Regarding the cell culture conditions, a variety of substrates, predominantly poly-l-lysine [36, 57, 140], poly-l-ornithine with/without lamin [147], gelatin [4, 47], and more rarely other substrates, have been used, while in most studies direct culture in culture-treated polystyrene [61, 125, 135, 137, 138, 141, 144] forms the commonest practice. However, the absence of comparative studies makes conclusions about the superiority of one substrate over the other impossible.…”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the cell culture conditions, a variety of substrates, predominantly poly-l-lysine [36, 57, 140], poly-l-ornithine with/without lamin [147], gelatin [4, 47], and more rarely other substrates, have been used, while in most studies direct culture in culture-treated polystyrene [61, 125, 135, 137, 138, 141, 144] forms the commonest practice. However, the absence of comparative studies makes conclusions about the superiority of one substrate over the other impossible.…”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%
“…Regarding the neuroinductive culture media, most studies use either the Neurobasal A or conventional primarily Dulbecco's Modified Eagle's Medium (DMEM)/F12 media in their neural differentiation protocols. These are used in conjunction with various neural supplements (most commonly the B27 [36, 125, 142, 144, 148, 149], but also the N2 consisting of a mixture of insulin, transferrin, progesterone, selenium, and putrescine [137] and the insulin-transferrin-selenium (ITS) supplement [54] or their combinations [143]) in a serum-free approach. Alternatively, in other studies, the media are supplemented with conventional fetal calf (FCS) or Fetal Bovine Serum (FBS) at least for the first-stage preincubation phase [135].…”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%
“…In 2000, a new group of adult mesenchymal stem cells, namely as dental stem cells were found to be the source of embryonic and mesenchymal cells with different biological characteristics [456]. These cells can be derived from human dental pulp and periodontal ligament.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research had shown that the dental pulp tissue of adult teeth contained neural-crest derived DPSCs, which expressed neural stem cell markers such as Nestin and GFAP 4,11 . Moreover, these were fully viable after one month post-graft and capable of in vitro differentiating into mesenchymal cell lineages and generating a dentin pulp-like tissue complex, after in vivo subcutaneous transplantation 3 .…”
Section: Neurocult Proliferation Mediamentioning
confidence: 99%